High performance solid state flexible supercapacitor based on molybdenum sulfide hierarchical nanospheres - Javed, Muhammad Sufyan; Dai, Shuge; Wang, Mingjun; Guo, Donglin; Chen, Lin; Wang, Xue; Hu, Chenguo; Xi, Yi (Journal of power sources, 2015)
Molybdenum sulfide (MoS2) hierarchical nanospheres are synthesized using a hydrothermal method and characterized by X-ray powder diffraction, Brunauer–Emmett–Teller, scanning electron microscopy and transmission electron microscopy. The prepared MoS2 is used to fabricate solid state flexible supercapacitors which show excellent electrochemical performance such as high capacitance 368 F g−1 at a scan rate of 5 mV s−1 and high power density of 128 W kg−1 at energy density of 5.42 Wh kg−1. The fabricated supercapacitor presents good characteristics such as lightweight, low cast, portability, high flexibility, and long term cycling stability by retaining 96.5% after 5000 cycles at constant discharge current of 0.8 mA. Electrochemical impedance spectroscopy (EIS) results reveal low resistance and suggest that MoS2 nanospheres would be a promising candidate for supercapacitors. Three charged supercapacitors connected in series can light 8 red color commercial light emitting diodes (LEDs) for 2 min, demonstrating its capability as a good storage device. A flexible solid state supercapacitor based on MoS2 hierarchical nanospheres shows excellent electrochemical performance and high specific capacitance of 368 Fg−1 at scan rate of 5 mVs−1 with long term cycling stability, demonstrating its capability as a good storage device. [Display omitted] •MoS2 hierarchical nanospheres are used for the first time to make supercapacitor on carbon cloth.•A flexible solid state supercapacitor based on MoS2 hierarchical nanospheres shows excellent electrochemical performance.•High specific capacitance of 368 Fg−1 at scan rate of 5 mVs−1 is achieved with long term cycling stability.•The flexible supercapacitor has almost same performance in different bending angles.